Across and beyond the devide : the role of interdepartmental teaching in bioinformatics - Mohd Shahir Shamsir,; Zeti Azura Mohamed Hussein, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Bioinformatics is a multidisciplinary field derived from computational and biological sciences. Its multidisciplinary nature has created a niche for specialists trained in both biology and computing, and it has required distinct teaching cooperation from experts in these two different areas. Consequently, teaching bioinformatics will require specialist educators with in-depth knowledge of the two different components -- biology and computer science. Because this is quite a daunting task, most universities lack the necessary specialists and experienced bioinformatics staff. They must therefore resort to the logical route of interdisciplinary and cross-faculty teaching. However, interfaculty teaching subsequently raises the issue of ‘ownership’, and consequently creates concerns regarding teaching and learning cultures, as it is obvious that each discipline has an its own inherent culture. In this article, we examined the curricula and their implementations at two Malaysian universities. Because both universities place their bioinformatics courses in opposing departments, we aimed to study how educators overcome the interdisciplinary barrier. In addition, we concisely explain the components that constitute the bioinformatics field, analyse the unique education criteria that are required to produce individuals with bioinformatics training and provide an overview of global bioinformatics education to further improve our implementation of bioinformatics education